The development of multiple objective programming methods for forest land management planning a survey and evaluation. - Bare, B. Bruce
Multiple objective programming (MOP) has undergone a rapid period of development in the 1970's. Concurrently, increased land-use pressures have stimulated forest land management analysts to develop and utilize more sophisticated planning aids to address complex multiple use issues involving multiple objectives and decision makers. In this paper, a selected set of MOP methodologies are reviewed and evaluated in terms of their utility and applicability as land management planning tools. The STEP method is selected as an appropriate technique and is applied to a forest land management problem. Two objective function weighting procedures are illustrated. Although no MOP technique by itself can resolve land management conflicts, the STEP method offers promise as a rational systematic means of exploring alternative feasible solutions to the multiple objective forest land management problem. Two objective function weighting procedures are illustrated. Although no MOP technique by itself can resolve land management conflicts, the STEP method offers promise as a rational systematic means of exploring alternative feasible solutions to the multiple objective forest land management problem. Multiple Objective Programming (MOP) or Multi-Criteria Decision Making (MCDM) is concerned with planning problems in which several conflicting objectives are to be optimized simultaneously. Multiple use forest planning exemplifies this situation because most forest land use planning problems involve a consideration of multiple conflicting goals and objectives such as : increased net revenue from timber resources, improved water quality, protection of wildlife, preservation of natural beauty, and increased recreational opportunities. The satisfactory attainment of these objectives is a major concern in forest land management planning. The applicability of MOP as a planning tool for forest land management planning is the primary motivation of this paper.